Math games for kids ebook 25+ fun, hands-on activities for learning with shapes, puzzles, and games. - Rapoport, Rebecca (Little Learning Labs., 2019)
Little Learning Labs: Math Games for Kids —an abridged paperback edition of Math Games Lab for Kids —presents 25+ hands-on activities that include coloring, art, puzzles, and more that make learning about math fun. Explore geometry and topology by building, drawing, and transforming shapes. Discover how to color maps like a mathematician by using the fewest colors possible. Draw graphs to learn the language of connections. Create mind-bending fractals with straight lines and repeat shapes. Everything you need to complete the activities can either be found in the book or around the house. The popular Little Learning Labs series (based on the larger format Lab for Kids series) features a growing list of books that share hands-on activities and projects on a wide host of topics, including art, astronomy, geology, math, and even bugs —all authored by established experts in their fields. Each lab contains a complete materials list , clear step-by-step photographs of the process, as well as finished samples . The activities are open-ended, designed to be explored over and over, often with different results. Geared toward being taught or guided by adults, they are enriching for a range of ages and skill levels. Gain firsthand knowledge on your favorite topic with Little Learning Labs. Open Little Learning Labs: Math Games for Kids and start exploring the exciting world of math!